Coproduction of healthcare service. Issue 7 (16th September 2015) - Batalden, Maren; Batalden, Paul; Margolis, Peter; Seid, Michael; Armstrong, Gail; Opipari-Arrigan, Lisa; Hartung, Hans
Abstract : Efforts to ensure effective participation of patients in healthcare are called by many names—patient centredness, patient engagement, patient experience. Improvement initiatives in this domain often resemble the efforts of manufacturers to engage consumers in designing and marketing products. Services, however, are fundamentally different than products; unlike goods, services are always 'coproduced'. Failure to recognise this unique character of a service and its implications may limit our success in partnering with patients to improve health care. We trace a partial history of the coproduction concept, present a model of healthcare service coproduction and explore its application as a design principle in three healthcare service delivery innovations. We use the principle to examine the roles, relationships and aims of this interdependent work. We explore the principle's implications and challenges for health professional development, for service delivery system design and for understanding and measuring benefit in healthcare services.